Looking for Easter - Chaconas, Dori 1938-; Moore, Margie (Morton Grove, Ill. : Albert Whitman & Co., 2008)
Little Bunny searches for Easter among the signs of spring in the forest.
Keywords: Easter -- Fiction; Spring -- Fiction; Rabbits -- Fiction; Animals -- Fiction -- Infancy; Friendship -- Fiction